Słoweńskie tłumaczenia literatury polskiej w latach 2019 i 2020 - Rezoničnik, Lidija; Borowy, Joanna; Gawlak, Monika (Przekłady Literatur Słowiańskich, 2022)
The article provides an overview of Slovenian translations of Polish literature in the 2019’s and 2020’s and reviewers’ responses to these works. A total of 23 translations of books were published in 2019, including five literary works (three collections of poetry and two novels). Among the 13 published translations of the following year there were eight literary works (one drama, a collection of short stories, three novels and three collections of poetry). The publishing of e-books also increased significantly in 2020. The published translations give Slovenian readers access to familiar, mostly world-renowned authors such as O. Tokarczuk, Z. Herbert, W. Szymborska, C. Miłosz, I. Karpowicz, while works by I. Ostachowicz, B. Nowicka, A. Kulisiewicz, J. Małecki, R. Franczak, and K. Dąbrowska were translated into Slovenian for the first time. With the exception of J. Kochanowski’s drama, all of the literary works translated were from the second half of the 20th century or the 21st century.